Effect of Air Humidity on the Evolution of Permeability and Performance of a Fibrous Filter during Loading with Hygroscopic and Non-hygroscopic Particles - Miguel, A. F. (2012)
A model was developed to predict the permeability and performance (i.e., the product of the permeability by the number of aerosol particles caught per unit surface) of a fibrous filter in dynamic regime. Besides the mass loading of the aerosol particles, this model took into account the structural characteristics of the filter, the size of the loading particles and the filtration velocity. An experimental filtration study was carried out to obtain the necessary input data for a comprehensive estimation of some relevant parameters of the model and to verify it. This study was performed with sodium chloride and alumina aerosols in the size range of 0.5–1.3 micron and 0.8–6 micron, respectively, and <ration velocities of 2, 5 and 15 cm/s. The relative air humidity was controlled in the range of 32–90%. It was observed that the permeability and the performance of tested filter were not only influenced by the size of aerosol particle and mass loading of particles but also by the particle hygroscopicity and air humidity, through the interdependence of this quantities with cake particle density. Furthermore, the filter was found to be more efficient when it operated at high humidities, except for sodium chloride particles at humidities above the deliquescent point.